2000
DOI: 10.1562/0031-8655(2000)072<0513:iopetb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Photosynthetic Electron Transport by UV-A Radiation Targets the Photosystem II Complex¶

Abstract: We have studied the inhibition of photosynthetic electron transport by UV-A (320-400 nm) radiation in isolated spinach thylakoids. Measurements of Photosystem II (PSII) and Photosystem I activity by Clark-type oxygen electrode demonstrated that electron flow is impaired primarily in PSII. The site and mechanism of UV-A induced damage within PSII was assessed by flash-induced oxygen and thermoluminescence (TL) measurements. The flash pattern of oxygen evolution showed an increased amount of the S0 state in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 30 publications
5
47
0
Order By: Relevance
“…We do not know if this occurs in Nannochloropsis under our experimental conditions, but it is possible that in a similar way, Z accumulation could be a response to a decrease in PSII activity because of direct UVR damage (Renger et al 1986, Trebst and Depka 1990, Turcsanyi and Vass 2000. In contrast, Pfü ndel et al (1992) argued that PSII inhibition by UVR could result in oxidation of electron carriers between photosystems, which reduces V availability, decreasing Z formation (Pfü ndel et al 1992, Siefermann andYamamoto 1975).…”
Section: Discussionmentioning
confidence: 84%
“…We do not know if this occurs in Nannochloropsis under our experimental conditions, but it is possible that in a similar way, Z accumulation could be a response to a decrease in PSII activity because of direct UVR damage (Renger et al 1986, Trebst and Depka 1990, Turcsanyi and Vass 2000. In contrast, Pfü ndel et al (1992) argued that PSII inhibition by UVR could result in oxidation of electron carriers between photosystems, which reduces V availability, decreasing Z formation (Pfü ndel et al 1992, Siefermann andYamamoto 1975).…”
Section: Discussionmentioning
confidence: 84%
“…Remarkably, a significantly lower DF=F 0 m in plants exposed to PAR supplemented with UV-A (PA) compared to plants exposed to the whole radiation spectra (PAB) and PAR-only treatment was observed. UV-A irradiation is reported to be damaging for PSII, affecting electron transport at the water-oxidizing complex and the binding site of the Q B quinine electron acceptor (Turcsá nyi and Vass, 2000). UV-A can also damage the catalytic manganese cluster of the wateroxidizing complex (Vass et al, 2002).…”
mentioning
confidence: 99%
“…He et al (1993) observed that decrease in the ratios of variable to maximum chlorophyll fluorescence yield and in the quantum yield of photosynthetic oxygen evolution by supplemental UV-B in pea and rice leaves. In contrast to UV-B, UV-A is not usually regarded as a potentially damaging stress factor, although Turcsanyi and Vass (2000) reported the UV-A induced impairment of photosystem II and concluded that UV-A radiation is highly damaging for PSII, and affected the electron transport at both the water oxidizing complex, and the binding site of the QB quinone electron acceptor in a similar way to that caused by UV-B radiation. Hakala-Yatkin, Mäntysaari, Mattila, & Tyystjärvi (2010) studied the contribution of the UV part of sunlight in photoinhibition of PSII in leaves and also suggested that especially the UV-A part, are potentially highly important in photoinhibition of PSII by the means a UV-permeable or UV-blocking filters.…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%